Data Analytics of Illegal Wildlife Trading in Cyberspace - Dr.N.Kala; Premanand Narasimhan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
India is one of the most bio-diverse Nation. Organised illegal wildlife trafficking and poaching poses threat as it creates an imbalance in the ecosystem as such. In case this situation continues some species will soon become extinct. The major legislative framework in India for addressing wildlife crime is the Wild Life (Protection) Act of 1972. The methods, strategies, and procedures employed by various Governments to look into wildlife crimes are inconsistent, which usually leads to problems with operations and the law. Diverse countries use different tactics, methodologies, and procedures to look into wildlife crimes, and this lack of consistency usually leads to operational and legal problems. Therefore, it is absolutely necessary to establish a clear-cut method for looking into wildlife infractions. Wildlife trafficking is becoming a serious concern to many plant and animal species as well. So much so, it has been classified as a subdivision of organised crime. Illegal wildlife is facilitated by the use of the internet. This paper focuses on data analytics of cybercrime investigation with a specific focus on wildlife trade.